Air pollution-related peak expiratory flow rates among asthmatic children in Chiang Mai, Thailand - Wiwatanadate P. (2014)
The severity of air pollution in northern Thailand has long been recognized; in spite of that there have been no epidemiological studies regarding the associations between the air pollution and health effects in the area. The authors followed a cohort of 31 asthmatic children (411 years of age) residing in Muang district, Chiang Mai, Thailand, from 29 August 2005 to 30 June 2006, for 306 days. The daily air pollutants, including particulate matter with aerodynamic diameter<2.5μm, particulate matter with aerodynamic diameter<10μm, carbon monoxide, ozone (O3), nitrogen dioxide, and sulfur dioxide (SO2), and the meteorological parameters, including pressure, temperature, relative humidity, rain quantity, and sunshine duration, were recorded. The peak expiratory flow rates (PEFRs) were fitted with pollutants and meteorological covariates using general linear mixed models to account for random effects and autocorrelation. The authors found that there were inverse associations of SO2 and evening PEFR, with a coefficient of -2.12 (95% confidence interval (CI)-3.22 to -0.28); of SO2 and daily percent deviation of PEFR, with a coefficient of -0.73 (95% CI-1.33 to -0.12); and of O3 combining with SO2 and daily average PEFR, with a coefficient of -0.16 (95% CI-0.31 to -0.00) and -1.60 (95% CI-3.10 to -0.11), respectively. The associations of O3 and SO2 with PEFR were found even when SO2 concentrations never exceeded the standard level.